2023
DOI: 10.5005/jp-journals-10071-24567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Neutralization Potential of Naja naja and Daboia russelii Snake Venom by Root Extract of Cyanthillium cinereum

S Suji,
MD Dinesh,
KU Keerthi
et al.

Abstract: A bstract Aim One of the main reasons for the death due to snake bites is the non-availability of antivenoms in the regions where they are needed. The use of medicinal plants and plant-based natural products as an alternative to antivenom will become a milestone in snake bite envenomation. The present study investigates the in vitro antivenom properties of Cyanthillium cinereum root extracts. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Suji et al [143] demonstrated that the hemolysis caused by the venoms of Daboia russelii and Naja naja was alleviated by an aqueous root extract of V. cinerea. The hemolysis of the venoms was decreased to 50% and 40%, respectively, and the extract also decreased the hemolytic halo produced by the venom.…”
Section: Antivenom Activitymentioning
confidence: 99%
“…Suji et al [143] demonstrated that the hemolysis caused by the venoms of Daboia russelii and Naja naja was alleviated by an aqueous root extract of V. cinerea. The hemolysis of the venoms was decreased to 50% and 40%, respectively, and the extract also decreased the hemolytic halo produced by the venom.…”
Section: Antivenom Activitymentioning
confidence: 99%